Development Of A Local Potential-Based Learning Model To Enhance Critical Thinking Skills - Sasmita, Rohmat Nugraha; Maryani, Enok; Sapriya, Sapriya; Anisah, Ani Siti (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2025)
This study aims to develop a local potential-based learning model to enhance elementary school students' critical thinking skills. Local potential-based learning is expected to utilize the wisdom and resources available in the surrounding environment as relevant and engaging learning materials for students. This learning model is designed to strengthen student involvement in the learning process, foster curiosity, and develop essential analytical and problem-solving skills for critical thinking. The approach involves integrating local materials, such as history, culture, and local social issues, into teaching activities. This study uses a simplified development method divided into three stages: preliminary study, development stage, and model effectiveness testing stage. The development stage begins with needs analysis, design, trial, and model evaluation. The research findings indicate that during the model evaluation stage, the effectiveness test results in SDN Bunikasih 1 as Experiment Class 1 reached an average % N-gain value of 55.05%, and model evaluation in Experiment Class 2 SDN Sukawangi 2 showed an average % N-gain value of 55.09%. Thus, the application of the local potential-based learning model is quite effective in helping improve students' critical thinking skills. The conclusion of this study is expected to contribute significantly to the development of a more contextual curriculum, enhance students' critical thinking skills, and encourage them to better understand and appreciate the local potential in their surroundings.